PENERAPAN GAME BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI CERITA ANAK SDN KUTA PASIE - Sinta; Syarfuni; Teuku Mahmud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the Game Based Learning (GBL) model in improving students' creative thinking skills in children's story material at SDN Kuta Pasie. The background of this study is based on the low level of student engagement and creative thinking skills in Indonesian language learning, which is still dominated by conventional methods. This condition causes students to be less active, less enthusiastic, and have difficulty understanding and developing ideas creatively. This research uses a qualitative approach with a descriptive method. The subjects of this study were third-grade students of SDN Kuta Pasie. Data collection techniques were carried out through observation, interviews, and documentation. The focus of the study includes the implementation process of GBL, student activities during learning, and students' creative thinking abilities after participating in the learning process. The results show that the implementation of Game Based Learning can create a more engaging, interactive, and enjoyable learning atmosphere. Students become more active in learning, more confident in expressing opinions, and able to develop creative ideas in composing children's stories. In addition, creative thinking indicators such as fluency, flexibility, originality, and elaboration have improved. Supporting factors include interesting learning media and active student participation, while inhibiting factors include limited time and student readiness. In conclusion, the implementation of Game Based Learning is effective in improving students' creative thinking skills in children's story material in elementary schools